Regulatory RNAs in Prokaryotes - Hess, Wolfgang R.; Marchfelder, Anita; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2012)
This book provides a comprehensive and up-to-date collection of review articles focusing on RNA-mediated regulation in prokaryotes. The various modes of action include the direct interaction with proteins, direct sensing of metabolites or of physical parameters, and the interaction with RNAs to stimulate or prevent binding of ribosomes or to stimulate degradation. Written by leading experts in the field, the book covers small RNA functions, RNA thermometers, riboswitches, the diversity of small RNA-guided CRISPR-Cas defense systems and selected RNA chaperons in both prokaryotic domains, bacteria and archaea. Recent advances towards the computational identification of regulatory RNAs and their targets are included and particular attention is paid to small RNA in pathogenic bacteria. This volume is the only one exclusively covering regulatory RNAs in the prokaryotic domains to date, making it essential literature for anyone interested in RNA function and gene regulation and a valuable resource for teaching these concepts.
Keywords: Life sciences; Nucleic acids; Biology -- Data processing; Microbial genetics; Life Sciences; Microbial Genetics and Genomics; Nucleic Acid Chemistry; Computer Appl. in Life Sciences